2016
DOI: 10.5130/ijcre.v9i1.4353
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental researcher attributes: Reflections on ways to facilitate participation in Community Psychology doctoral dissertation research

Abstract: As novice researchers, Community Psychology doctoral students encounter fresh challenges when they attempt to facilitate participation by members of the community in their dissertation projects. This article presents the merit in adopting fundamental researcher attributes, which have been described in published academic literature as personal characteristics that facilitate participation by members of the community in research studies. The value of these researcher attributes is exemplified in the discussion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…While CBPR projects uphold the community psychology values guiding those training to become community psychologists, additional recommendations for trainees and training programs have been presented in recent years (Jimenez et al, 2016;Liboro & Travers, 2016). Building on Liboro and Travers'(2016) call for creative resourcefulness in community psychology work and CBPR, we believe that researchers training in community psychology would benefit from considering and evaluating digital technologies as potentially powerful and creative resources.…”
Section: Digital Technologies and Cbprmentioning
confidence: 98%
See 1 more Smart Citation
“…While CBPR projects uphold the community psychology values guiding those training to become community psychologists, additional recommendations for trainees and training programs have been presented in recent years (Jimenez et al, 2016;Liboro & Travers, 2016). Building on Liboro and Travers'(2016) call for creative resourcefulness in community psychology work and CBPR, we believe that researchers training in community psychology would benefit from considering and evaluating digital technologies as potentially powerful and creative resources.…”
Section: Digital Technologies and Cbprmentioning
confidence: 98%
“…Similar calls for interdisciplinary work have highlighted the importance of achieving a systematic change in health services, and research has suggested that strategic partnerships should be fostered across discipline silos, such as those in the health and social sciences (Dooris, 2013), particularly in their CBPR work. A recent review of vital researcher qualities conducted by community psychologists noted the additional importance of creative resourcefulness among researchers to build stronger relationships with community partners and other collaborators in CBPR projects (Liboro & Travers, 2016).…”
Section: Using Cbpr To Promote Community Psychology's Engaged Scholar...mentioning
confidence: 99%